The conceptualisation of translation in translation studies: a response - Gambier Yves (Routledge Journals, Taylor & Francis Ltd, 2025)
"Translation" yesterday (in the 1980s and 1990s) was defined in a certain context. Today, in a more globalized and digitalized world, the concept is changing, becoming more fluid while scholars in TS are becoming more nomadic (in their affiliations, and between disciplines). To avoid as much as possible a terminological inflation in TS and a monolithic and static concept of translation, we must consider the socio-cultural context in which we try not only to define our object of investigation but also to clarify the purpose of our definition(s), considering the wide range of translators and interpreters with different status and working with different e-tools. In addition, a historical perspective is needed: two paradigms are changing, sometimes overlapping. Thus, the feeling of confusion.